Factors influencing treatment outcomes in tuberculosis patients in Limpopo Province, South Africa, from 2006 to 2010: A retrospective study - Mohammed M. Gafar; Norman Z. Nyazema; Yoswa M. Dambisya (AOSIS, 2014)
Background: South Africa has a high burden of tuberculosis (TB), with high human immunodeficiency virus (HIV)-TB co-infection rates and the emergence of multidrugresistant TB. Objectives: To describe treatment outcomes and factors influencing outcomes amongst pulmonary TB (PTB) patients in the Limpopo Province. Method: A retrospective review was conducted of data on the provincial electronic TB register (ETR.net) for the years 2006 to 2010 (inclusive), and a random sample of 1200 records was selected for further analysis. The Chi square test was used to examine the influence of age, gender, health facility level, diagnostic category and treatment regimen on treatment outcomes. Results: Overall 90 617 (54.6% male) PTB patients were registered between 2006 and 2010. Of the sampled 1200 TB cases, 72.6% were in persons aged 22 to 55 years and 86.2% were new cases. The TB mortality rate was 13.6% (much higher than the World Health Organization target of 3%), whilst the default rate was 9.8%. There was a strong association between age (P < 0.001), diagnostic category (P < 0.001), treatment regimen (P < 0.001), and health facility level (P < 0.001) and treatment outcome. Those aged 22-55, and 56-74 years were more likely to die (P < 0.05). Poor treatment outcomes were also associated with initial treatment failure, receiving treatment at hospital and treatment regimen II. Conclusion: The poor TB treatment outcomes in Limpopo, characterised by a high mortality and default rates, call for strengthening of the TB control programme, which should include integration of HIV and/or AIDS and TB services.